2012
DOI: 10.1159/000338124
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of in vitro Culture of Fetal Nucleated Erythroblasts from Fetal Chorionic Villi and Maternal Peripheral Blood for Noninvasive Prenatal Diagnosis

Abstract: Objective: We tested the feasibility of the in vitro culture of fetal nucleated erythroblasts from maternal blood for noninvasive prenatal screening as a substitute for culturing fetal nucleated erythroblasts from fetal villi. Method: Nucleated blood cells separated via Percoll from 52 samples of fetal villi and maternal peripheral blood were cultured with or without magnetic-activated cell sorting glycophorin A (MACS-GPA+), and detected by an anti-hemoglobin-epsilon (FITC) antibody. Gender of the epsilon-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…One limitation to our study is that due to the rarity of hEryPs in maternal blood, we opted to study hEryPs from placental villi. It has been demonstrated that there are significantly higher numbers of proerythroblasts and basophilic EryPs present in the villi; however, there are similar numbers of polychromatic and orthochromatic EryPs in villi and so we believe that although there are undoubtedly differences in the composition of the cells in the 2 compartments, the fact that we only select epsilon globin‐positive cells for NIPD means that we are still examining the hEryP cell type.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One limitation to our study is that due to the rarity of hEryPs in maternal blood, we opted to study hEryPs from placental villi. It has been demonstrated that there are significantly higher numbers of proerythroblasts and basophilic EryPs present in the villi; however, there are similar numbers of polychromatic and orthochromatic EryPs in villi and so we believe that although there are undoubtedly differences in the composition of the cells in the 2 compartments, the fact that we only select epsilon globin‐positive cells for NIPD means that we are still examining the hEryP cell type.…”
Section: Discussionmentioning
confidence: 98%
“…Only a single fetal cell per mL of blood may be retrieved following enrichment . Attempts to expand the numbers of fetal cells by culture have been mostly unsuccessful due to contamination with maternal cells . Characterization of surface antigens, surface charge, and buoyant density have all been investigated to find ways to enhance the cell enrichment process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few fetal cells required together with the use of automatic scanning for the detection of fetal cells [73] and SCs-WGA will help to overcome the problem of rarity of these cells in the maternal blood and make their use in NIPD much more easily achievable. Although this method is not yet completely mature due to the absence of a perfect antigen that can recognize 100% of fetal cells, relentless efforts continue and should lead to the development of this antigen in the near future [74,75]. However, this protocol will still be feasible with the available markers that recognize specific types of fetal cells as the fetal trophoblasts or normoblasts, but probably with a larger amount of maternal blood as there is no general agreement about their exact frequencies per ml of maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, NRBC are commonly present in the peripheral blood even in healthy individuals. Prove has been provided consistently throughout the decades by non-invasive pre-natal testing (NIPT) [114,115] and recent investigations on rare cells in peripheral blood [2,10] Most explanations for the presence of NRBC in the peripheral blood relate to impaired erythropoiesis that has been divided into three categories; inefficient erythropoiesis for example caused by thalassemia, stress induced erythropoiesis for example erythropoietic resumption after chemotherapy, and pathological erythropoiesis due to primary abnormalities in hematopoiesis (for example caused by various leukemias). In general pathological erythropoietic activity is considered a consequence of hypoxic stress [113,116].…”
Section: Circulating Erythroblastsmentioning
confidence: 99%